Identification and verification of hybridoma-derived monoclonal antibody variable region sequences using recombinant DNA technology and mass spectrometry. (October 2017) - Babrak, Lmar; McGarvey, Jeffery A.; Stanker, Larry H.; Hnasko, Robert
Highlights: Sequential workflow for the identification and confirmation of MAb VR. Selective PCR amplification of MAb VR sequences from hybridomas. Tandem MS/MS for confirmation of MAb VR from a predictive VR sequence. Abstract: Antibody engineering requires the identification of antigen binding domains or variable regions (VR) unique to each antibody. It is the VR that define the unique antigen binding properties and proper sequence identification is essential for functional evaluation and performance of recombinant antibodies (rAb). This determination can be achieved by sequence analysis of immunoglobulin (Ig) transcripts obtained from a monoclonal antibody (MAb) producing hybridoma and subsequent expression of a rAb. However the polyploidy nature of a hybridoma cell often results in the added expression of aberrant immunoglobulin-like transcripts or even production of anomalous antibodies which can confound production of rAb. An incorrect VR sequence will result in a non-functional rAb and de novo assembly of Ig primary structure without a sequence map is challenging. To address these problems, we have developed a methodology which combines: 1) selective PCR amplification of VR from both the heavy and light chain IgG from hybridoma, 2) molecular cloning and DNA sequence analysis and 3) tandem mass spectrometry (MS/MS) on enzyme digests obtained from the purified IgG. Peptide analysis proceeds by evaluating coverage of the predicted primary protein sequence provided by the initial DNA maps for the VR. This methodology serves to both identify and verify the primary structure of the MAb VR for production as rAb.